QUANTUM CHEMICAL MODELLING OF SYN-ANTI ISOMERIZATION IN SUBSTITUTED ALLYL-NICKEL COMPLEXES - F. O. Danilov; R. S. Shamsiev (Тонкие химические технологии)
The syn-anti isomerization of bis-(η3 -allyl)nickel complexes (allyl – C3H5, 2-CH3C3H4, 1-CH3C3H4) has been studied using the density functional theory (DFT-PBE). Calculations indicated that in all cases isomerization goes through 3 steps according to η3 -η1 -η3 -mechanism. The rate-limiting step of that is vinyl fragment rotation in η1 -allyl ligand.